EMPLOYEE PERFORMANCE: THE ROLES OF WORK DISCIPLINE, OCCUPATIONAL SAFETY AND HEALTH, AND WORK ENVIRONMENT - Amalia Zakirah; Yandra Rivaldo; Netti Syafitri; Robby Kurniawan (ZILLZELL MEDIA PRIMA, 2026)
This study aims to analyze the effects of work discipline, occupational safety and health, and work environment on employee performance at PT Armada Lintas Samudra. The study used a quantitative approach with PT Armada Lintas Samudra as the research object. The population consisted of 37 permanent employees, and all of them were selected as the sample using total sampling. Data were collected through an online closed-ended questionnaire using a five-point Likert scale and were analyzed using SPSS. The analysis techniques included validity and reliability tests, classical assumption tests, multiple linear regression, t-test, F-test, and coefficient of determination. The results showed that work discipline had a positive and significant effect on employee performance, as indicated by a significance value of 0.011. Occupational safety and health also had a positive and significant effect on employee performance, with a significance value of 0.026. However, work environment did not have a significant partial effect on employee performance, as its significance value was 0.103. Simultaneously, work discipline, occupational safety and health, and work environment had a significant effect on employee performance, with an F-value of 12.101 and a significance value of 0.000. The model explained 48.1% of the variation in employee performance. These findings indicate that improving employee performance requires strengthening work discipline and optimizing occupational safety and health implementation within the company.